Evaluation of the platelet volume index as a prognostic factor after aneurysmal subarachnoid hemorrhage - Dündar, Tolga Turan; Kitiş, Serkan; Abdallah, Anas; Yurtsever, İsmail and Gülen, Bedia (Journal of Surgery and Medicine, 2019)
Aim: Subarachnoid Hemorrhage (SAH) originating from an intracranial aneurysm is a severe and life-threatening disease, witnessed by physicians in Emergency Departments (ED). Despite the improvements in diagnostic and therapeutic techniques, morbidity and mortality rates of SAH remain high. Several parameters based on biochemical analysis and imaging techniques are used to evaluate the prognosis. However, efforts for identifying an ideal marker have not been successful. For many years, Fisher Grading System, which is based on computerized tomography (CT), has been used as a reliable predictive scale to identify SAH. Besides, the immune response plays an active role in determining neuro-damage after SAH. Recently, Mean platelet volume (MPV) to platelet count (PLT) ratio has become a trend indicator to anticipate the outcome of a patient suffering from SAH. This study aims to determine whether the comparison of the immune response marker [Platelet Volume Index (PVI)] with the Fisher Grading System could be used as a prognostic factor in subarachnoid hemorrhages with ruptured intracranial aneurysms. Methods: In this retrospective cohort study, 52 patients diagnosed with spontaneous SAH in the ED were included. The patients’ ages, genders, Fisher grades, locations of the ruptured aneurysm, PVI and Glasgow Coma Scale (GCS) scores were recorded. MPV:PLT ratio was defined as MPV value(fL) x100 /PLT (per 1000). Each patient’s GCS at the time of their admission to the ED was noted. An experienced radiologist graded their initial CT scans immediately according to the Fisher Grading System. Patients’ GCS scores were noted by the investigators and PVI was calculated. A retrospective review was carried out regarding medical records of age, sex, and other conditions. The Pearson Correlation Coefficient was used in the analysis of the interrelationship. Results: The correlation among the PVI with GCS and Fisher Grade test was found to be positive statistically correlation. Relevant literature establishes the same result. Additionally, analyses established a significant positive correlation between the Fisher Grading Scale and the PVI among the data of ruptured aneurysms. Conclusion: The PVI can be used as a prognostic, predictive factor for SAH. Nevertheless, further studies concerning the prognosis of SAH are needed to confirm this hypothesis.